Combat, Casualties, and Compensation: Evidence from Iraq and Afghanistan - Laura Armey; Thomas J. Kniesner; John D. Leeth; Ryan Sullivan (Institute of Labor Economics (IZA), 2018)
Our research examines the effect of combat deployments to Iraq and Afghanistan on casualties. We use restricted data from the Defense Manpower Data Center (DMDC) and Social Security Administration (SSA) to construct a panel of all U.S. Active Duty service members having served at some point during the years 2001-2012. Casualties disproportionately occur at higher rates among (i) young, white, males (ii) enlisted personnel (iii) less educated personnel (iv) and those in combat job types. Our estimates indicate that overall U.S. military personnel who deployed in an individual year to Iraq or Afghanistan had a 48 per 100,000 higher probability of death than non-deployed military personnel who remained stateside. The increased fatal injury risk of deployed U.S. military personnel is 15 times higher than the national average civilian workplace fatality rate, but roughly equal to the fatal injury risk faced in some of the most dangerous civilian occupations. Our estimates suggest a compensating wage differential equal to 808 per month would be appropriate, in comparison to the current status quo of 225 per month in danger pay (and additional tax benefits) provided to U.S. military personnel deployed into combat zones. The additional compensation should also be adjusted by service or job type.
Keywords: H56; J17; J28; J31; 330; military; deployment; VSL; casualties; danger pay